Teaching and Leaning in.a Multicultural society A educational phitosophical approach - Fernando, R.A.N. (Global Research and Development Services, 2017)
Attached

The purpose of this research paper is to define the concept of multicultural education and multicultural education as a philosophy to be followed by the present system of education in metropolitan world. Multicultural education is a philosophical concept buitt on the ideals of freedom, justice, equality, equity, and human dignity as acknowledged in various documents, such as the u.S. Declaration of Independence, universal Declaration of Human rights adopted by the United Nations. It affirms our need to prepare student for their responsibilities in an interdependent world. It recognise what sort of role schools can pay in developing the attitudes and values necessary for a democratic society. It values cultural differences and affirms the pluralism that students, their communities, and teachers reflect. It challenges all forms of discrimination in schools and soeiety through the promotiou of democratic principles of social justice. Multicultural education is a process that permeates all aspects of school practices, policies and organization as a means to ensure the highest levels of academic achievement for all students. It helps students develop a positive self-concept by providing knowledge about the histories, cultures, and contribufions of diverse groups. It prepares all students to work actively toward structural equality in organizations and insti(utions by providing the knowledge, dispositions, and skills
Keywords: Education, Multiculturalism, Freedom, Teaching, Learning